“Integrating Cultural Heritage in Visual Arts Lessons to Enhance Students’ Creative Thinking” - Nasulloyeva Sarvinoz Komiljon qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article explores the integration of cultural heritage into visual arts lessons as a means to enhance students’ creative thinking, aesthetic literacy, and artistic competencies. It highlights the importance of traditional art forms in developing a connection to national culture and identity. The study examines practical, project-based, and interactive teaching strategies that enable students to apply traditional artistic elements in contemporary visual art projects, fostering creativity and innovation.